2014
DOI: 10.3892/or.2014.3221
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of flotillin-1 is involved in proliferation and recurrence of bladder transitional cell carcinoma

Abstract: Flotillin-1 (FLOT1) is known to have a role in tumorigenesis; however, the effect of FLOT1 on proliferation and recurrence of human transitional cell carcinoma (TCC) is unclear. Samples from 156 TCC patients and 142 patients undergoing open bladder surgery for indications other than TCC were used in the present study. FLOT1 protein expression was determined by immunohistochemistry and western blot analysis, and mRNA expression was detected by RT-PCR and real-time PCR. A FLOT1-expressing pcDEF3 vector was stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…There were two high scoring binding sites of miR-608 on the 3′-UTR of FLOT1 mRNA. It has been reported that FLOT1 was the upstream regulator of AKT/FOXO3a pathway in renal cell cancer and the proliferation regulator in BCa and breast cancer [31, 38, 39]. In our study, we discovered that FLOT1 was widely over-expressed in bladder cancer TMAs (Fig.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…There were two high scoring binding sites of miR-608 on the 3′-UTR of FLOT1 mRNA. It has been reported that FLOT1 was the upstream regulator of AKT/FOXO3a pathway in renal cell cancer and the proliferation regulator in BCa and breast cancer [31, 38, 39]. In our study, we discovered that FLOT1 was widely over-expressed in bladder cancer TMAs (Fig.…”
Section: Resultssupporting
confidence: 51%
“…In addtion, FLOT1 was primarily known as a cell signaling mediator by anchoring various receptors of signaling pathways onto cell membrane [48, 49]. Previous studies showed that FLOT1 was constantly overexpressed in various cancers such as colorectal tumor, esophageal squamous carcinoma, tongue squamous carcinoma, prostate cancer, bladder transitional cell carcinoma, renal cell carcinoma and breast cancer [31, 3840, 5052]. Moreover, the overexpression of FLOT1 could dramatically promote the proliferation of prostate and bladder cancer cells, and also accelerate the invasion, migration of bladder cancer cells [38, 52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,21 Recent studies have revealed that flotillin-1 has important roles in the progression of several tumor types, including hepatocellular carcinoma, 22 neuroblastoma, 23 breast cancer, [24][25][26] tongue squamous cell cancer, 27 esophageal squamous cell carcinoma, [28][29][30] prostate cancer, 19 NSCLC, 5,31,32,33 renal cell carcinoma 34 and bladder transitional cell carcinoma. 35 Zhang SH et al have reported that a high level of flotillin-1 expression is associated with disease progression and poor prognosis in patients with hepatocellular carcinoma. 22 Consistently, our previous study revealed that upregulation of flotillin-1 expression in human LUAD tissues is significantly correlated with advanced clinical stage, lymph node metastasis, increased postoperative relapse and decreased overall survival.…”
Section: Introductionmentioning
confidence: 99%